2012
DOI: 10.1002/anie.201204452
|View full text |Cite
|
Sign up to set email alerts
|

Genuine Redox Isomerism in a Rare‐Earth‐Metal Complex

Abstract: Redox isomerism is observed for a lanthanide complex for the first time. Upon lowering the temperature, an electron of [{(dpp-bian)Yb(μ-Cl)(dme)}(2)] (1) is transferred from the metal to the ligand (see picture), giving rise to marked shortening of Yb-N bonds and a hysteretic jump in the magnetic moment. The crystal packing is of a crucial importance, as two other crystal modifications of 1 do not undergo this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(65 citation statements)
references
References 14 publications
1
60
0
Order By: Relevance
“…2b) 64 . Because of the metal-to-ligand charge transfer, the redox state of the metal centres in the dinuclear Yb 2 complex changes from Yb III Yb III at LT to Yb III Yb II at HT.…”
Section: Charge Transfermentioning
confidence: 98%
“…2b) 64 . Because of the metal-to-ligand charge transfer, the redox state of the metal centres in the dinuclear Yb 2 complex changes from Yb III Yb III at LT to Yb III Yb II at HT.…”
Section: Charge Transfermentioning
confidence: 98%
“…While redox-active ligands have been proven to impart interesting magnetic [8,9] or electrochemical [10][11][12] properties to the rare earth elements due to their ability to stabilize ligand radicals, [13,14] fewer examples exist that demonstrate productive electron movement for new bond formation. Mazzanti et al reported tetradentate Schiff base complexes of Nd, Eu, Tb,Ybthat, upon reduction, store two electrons in anew CÀC s bond.…”
mentioning
confidence: 99%
“…To the besto fo ur knowledge, the reactiono ft his ligand with lanthanide halogenides has so far not been reported in a3:1 stoichiometry. [13] Notably,s imilar vanadium complexes with ar elated ligand have been described previously. [14] As summarized in Scheme 1, the Ln(Ph-BIAN) 3 compounds were obtained in high yields.…”
Section: Resultsmentioning
confidence: 99%